Impact of Exchange Rate and Crude Oil Price on the Nigeria Economic Growth - Ajagbe, Surajdeen Tunde; Olanipekun, Wahid Damilola; Abdulkadri, Mustapha; Adegboye Ayodeji, Hakeem; Olajide Olusegun, Abatan (Acta Universitatis Danubius. Œconomica, 2024)
This study investigates the impact of exchange rate and oil price on economic growth in Nigeria. The study uses growth rate as a proxy for economic growth and combines crude oil price, exchange rate, and interest rate as independent variables. Annual time-series data from 1990 to 2023 was gathered from secondary sources, including the World Development Indicators, Central Bank of Nigeria Statistics, and OPEC database. The data was analyzed using a variety of statistical methods and procedures, including descriptive statistics, unit root tests, correlation analysis, serial correlation tests, heteroskedasticity tests, and normality tests. The results reveal a weakly negative association (-0.0906) between growth rate (GR) and Nigeria's exchange rate (EXR), indicating that the growth rate tends to decline significantly as the exchange rate increases. Conversely, the strong positive connection suggests that GR in Nigeria is significantly impacted by changes in the currency rate. Additionally, the study finds a weakly positive correlation (0.2221) between the price of crude oil (COPr) and GR, suggesting that the growth rate tends to increase to some extent in tandem with an increase in the price of crude oil. GR and interest rate (INT) also have a 0.1155 weakly positive association. The Vector Error Correction (VEC) model results show that the first and second lags of the exchange rate changes have statistically significant positive effects, while the lags of the commodity price and interest rate changes do not appear to be statistically significant. The study also finds no evidence of serial correlation in the residuals of the VEC model at the tested lag orders.